The Relevance and Consistency of the Constitutional Court's Application of the Purcell Principle in Elections: Relevansi dan Konsistensi Penerapan Prinsip Purcell oleh Mahkamah Konstitusi dalam Pemilihan Umum - Azmi Fathu Rohman; Naufal Rizqiyanto; Muhammad RM Fayasy Failaq (Lex Renaissance, 2024)
Election regulations became rules that are most frequently changed through legislation or judiciary adjudication. These changes are sometimes made when the election stages have begun, which can cause polemics both in terms of election technicalities and in terms of the substance of election rules. In facing this, the application of the Purcell Principle by the Constitutional Court is considered to be a solution. However, the question is, this principle comes from a country with a different legal culture and election system from Indonesia. This study is here to examine the relevance of the Purcell Principle to the Indonesian general election system and to examine the consistency of the Constitutional Court's practice in applying this principle. This research is a normative legal research with a literature study. The approaches used are the case approach and the conceptual approach. The data and legal materials obtained will be analyzed qualitatively. The results of the study show that the Purcell Principle in the election system in Indonesia has urgency both technically and non-technically. To be relevant, this principle must become a legal culture that is carried out and applied by the Constitutional Court, starting from consistency and making several technical adjustments related to the time of application of this principle. Finally, in the practice of Constitutional Court Decision No. 102/PUU-VII/2009, Constitutional Court Decision No. 90/PUU-XXI/2023, and Constitutional Court Decision No. 116/PUU-XXI/2023 which is a test related to election law regulations shows that there have been differences and inconsistencies in the application of the Purcell Principle in Indonesia by the Constitutional Court.Keywords: Constitutional Court, Election, Purcell Principle AbstrakRegulasi pemilu merupakan aturan yang paling sering berubah baik melalui legislasi maupun ajudikasi oleh lembaga peradilan. Perubahan itu terkadang dilakukan ketika tahapan pemilu telah dimulai sehingga dapat menimbulkan polemik baik dari segi teknis pemilu maupun dari segi substansi aturan pemilu. Menghadapi itu, penerapan Prinsip Purcell oleh Mahkamah Konstitusi dinilai dapat menjadi solusi. Namun yang menjadi pertanyaan, prinsip tersebut hadir dari negara dengan budaya hukum dan sistem pemilu yang berbeda dengan Indonesia. Penelitian ini hadir untuk mengkaji relevansi Prinsip Purcell terhadap sistem pemilihan umum Indonesia serta mengkaji konsistensi praktik Mahkamah Konstitusi dalam penerapan prinsip tersebut. Penelitian ini merupakan penelitian hukum normatif dengan studi kepustakaan. Pendekatan yang digunakan adalah pendekatan kasus dan pendekatan konseptual. Adapun data dan bahan hukum yang diperoleh akan dianalisa secara kualitatif. Hasil penelitian menunjukkan bahwa Prinsip Purcell dalam sistem pemilu di Indonesia memiliki urgensitas baik secara teknis maupun non teknis. Agar relevan, prinsip tersebut harus menjadi budaya hukum yang dilakukan dan diterapkan oleh Mahkamah Konstitusi yang dimulai dari konsistensi dan dilakukan beberapa penyesuaian teknis terkait waktu penerapan prinsip tersebut. Terakhir, pada praktik Putusan MK No. 102/PUU-VII/2009, Putusan MK No. 90/PUU-XXI/2023, dan Putusan MK No. 116/PUU-XXI/2023 yang merupakan pengujian terkait aturan hukum pemilu menunjukkan bahwa telah terjadi perbedaan dan inkonsistensi penerapan Prinsip Purcell di Indonesia olah Mahkamah Konstitusi.Kata Kunci: Mahkamah Konstitusi, Pemilu, Prinsip Purcell